(Re)-programming typologies of public infrastructure to serve as a tool for cultural evolution: a re-imagination of the Cape Town Station - Schmidt Von Wühlisch, Jochen (School of Architecture, Planning and Geomatics, 2017)
This design dissertation aims to explore the Cape Town Station as an opportunity to support the social evolution that is on our doorstep. For this I chose to explore the balances in the concepts of culture, society and identity; and consequently the ideas of typology and programming within the infrastructure of a major railway station/public transport node. Individual and social identity is an omnipresent topic in the architectural discourse. Countless theories exist that attempt to understand the composition of identity; the lack thereof; the origin; the contestation and the evolution of what makes us US: a unique and conscious being that belongs. Navigating this vast topic of architecture + identity is not an easy task, and it is easy to attach to existing discourse within the larger field of discussion of aestetic and imageability. This dissertation therefore will approach the problem from a completely different angle, and will use the issue of identity in a post-apartheid South Africa as a basis to explore method of design that is appropriate for the Post-Apartheid context in South Africa.